KRITIK TERHADAP BUKU AL-‘ARABIYYAH AL-MU’ĀṢIRAH KARYA ECKEHARD SCHULZ - Aliwafa (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Book of al-‘Arabiyyah al-Mu’āṣirah by Eckehard Schulz  Indonesian  edition comes in conventional/print form and e-edition. The second edition can be operated on laptop, notebook, or tablet PC, and even completed with audio file that can be used by clicking the word or sentence. E-edition can be accessed on website www.modern-standart-arabic.comCriticism for book of al-‘Arabiyyah al-Mu’āṣirah are: First, the use of Indonesian by 21.355 words (31,65%) to explain the difficult words. The authors of the book should explain difficult words with pictures, antonysm, sinonysm, etc. Second, unnatural language skills. The order of Mahārat al-Lughah (language skills) in al-‘Arabiyyah al-Mu’āṣirah book started from reading, writing, listening and speaking skills, and then the second writing and speaking skills. Those order doesn’t match with the general order. Third, Grammar learning is positioned at the beginning of each lessons and gives impression of Arabic grammar or qirāah learning book. Fourth, the presentation of new mufradāt is very large in number, which is 1.406 in volume 1 alone. Fifth, there is no harokat. Book of al-‘Arabiyyah al-Mu’āṣirah doesn’t use harokat at all, even though harokat is really needed in learning process to accelerate the understanding of the contents of the book. Sixth, the appearance and presentation of the book is still lacking, there is no colourfull pictures, simple layout and cover, language game and the likes are not included. Seventh, muṣāhibat al-kitāb (book accompaniment) like exercise book, etc isn’t complete. Eighth, Indonesian Islamic culture isn’t accommodated. The book only displays some part of progress in the culture of the Arab world, but there is no comparison between Arab and non-Arab cultures such as Indonesia as it’s users. Displays of Indonesian Islamic cultures on the early chapters of the book would help and attract the readers.